1986
DOI: 10.1016/0014-5793(86)80988-7
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the electron spin polarization of the donor triplet state of the photosynthetic reaction center fromRhodopseudomonas viridisand the redox state of the primary acceptor

Abstract: The relation between the electron spin polarization of the donor triplet state of the photosynthetic reaction center from Rhodopseudomonas viridis and the redox state of the primary acceptor The hypothesis [( 1986) Photobiochem. Photobiophys. 11,95 -1001 that the temperature dependence of the electron spin polarization (ESP) pattern of the Am = k 1 EPR spectrum of the triplet state PR of the Rhodopseudomonas viridis reaction center is caused by magnetic interaction between the reduced menaquinoneiron complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

1987
1987
1990
1990

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
2
6
1
Order By: Relevance
“…When the ubiquinone is replaced by menaquinone, which couples magnetically much stronger to I; than UQ- (Okamura et al, 1979) the observed fraction is even lower: 0.5 at 100 K. Although the ESP pattern of PR for Rb. sphaeroides R-26 does not change with temperature, as previously reported (Van Wijk, 1986b), our present results demonstrate that its F-value does change with temperature.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…When the ubiquinone is replaced by menaquinone, which couples magnetically much stronger to I; than UQ- (Okamura et al, 1979) the observed fraction is even lower: 0.5 at 100 K. Although the ESP pattern of PR for Rb. sphaeroides R-26 does not change with temperature, as previously reported (Van Wijk, 1986b), our present results demonstrate that its F-value does change with temperature.…”
Section: Resultssupporting
confidence: 91%
“…sphaeroides R-26 has the same effect as a double reduction of MQ in Rps. viridis (Van Wijk et al, 1986b), as expected.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations